Biogas Dari Limbah Dan Prototype (Bagian 1) - Karsini Karsini (Balai Besar Kimia dan Kemasan, 1979)
Since 1977/1978 Industrial Research Institute Jakarta has become actively involved in the planning and operation of biogas plants, which recover meth ne gas and enriched fertilizer from livestock manure (pig manure) and organic waste. In 1978/1979 there bas been built a biogas digester unit at Kapuk , west Jakarta. And methane gas production has been used for lighting and cooking.